Human behavior and the social environment : integrating theory and evidence-based practice - Wodarski, John S.; Dziegielewski, Sophia F. (Springer series on social work (Unnumbered), 2002)
This comprehensive text offers a solid foundation for assessment of human behavior in micro, mezzo, and macro settings. The editors offer practical and concrete consideration of how human behavior is affected in different systems: individual, biological, family, community, and organizations. These influences are reviewed in terms of implications for practice.